134 Outcomes for patients with non-metastatic triple-negative breast. (18th September 2019) - Haddad, S; zemni, I; Bettaieb, I; ben Hassouna, J; Hechiche, M; Chargui, R; Rahal, K
Abstract : Objectives: We studied characteristics of patients with non metastatic TNBC and assessed survival outcomes and prognostic factors. Methods: We searched our Institute of Cancer registry database and identified patients with TNBC without distant metastatic disease. We retrieved demographic, tumour characteristic and treatment information. Locoregional recurrence-free survival, breast cancer-specific survival (BSS), metastasis-free survival (MRFS) and overall survival were determined.Predefined univariate and multivariate analyses were carried out investigating the association of survival outcomes with treatment and tumour characteristics. Results: In total, 275 patients were identified, with a median follow-up of 3.5 years. The median age was 55 years. Thirty-eight per cent were node positive and 79% were grade III. Mastectomy was carried out in 53%, adjuvant radiation delivered in 66% and chemotherapy in 69%. The significant predictive factors for overall survival, BSS and MRFS were radiotherapy, chemotherapy and neoadjuvant chemotherapy. The significant prognostic indicators were lymphovascular invasion, nodal status and tumour size. On KaplaneMeier analysis, the 5 year overall survival was 72%. The median time to death for those who died was 3.55 years with 92% of deaths within 5 years. Seventy-four per cent of patients had distant metastasis as a first recurrence and isolated local recurrences occurred in only 4.5%. Metastatic disease occurred in lung (55.9%) and was in multiple sites in 51%. Conclusions: Althought standard therapies are positively associated with survival outcomes particularly in the setting of recurrent disease the prognosis remains poor. Increased research into more effective systemic agents and the most effective timing of delivery of these may result in improved outcomes.